The The Effect of Buerger Allen Exercise on Peripheral Tissue Perfusion in Patients with Type 2 Diabetes Mellitus: A Literature Review - Adinda Dwi Susila Nugroho; Fahrun Nur Rosyid (STIKep PPNI Jawa Barat, 2026)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia due to impaired insulin secretion and/or insulin resistance. One of the most common long-term complications is impaired peripheral tissue perfusion of the lower extremities, which can progress to diabetic foot ulcers and significantly increase the risk of amputation. Consequently, identifying effective and accessible non-pharmacological interventions to improve peripheral circulation is crucial. Objective: This literature review aimed to evaluate the effectiveness of Buerger Allen Exercise (BAE) in improving peripheral tissue perfusion among patients with type 2 diabetes mellitus. Methods: A literature review was conducted using Google Scholar, PubMed, ScienceDirect, ProQuest, and Elsevier databases. Articles published between 2016 and 2024 were identified using the keywords “Buerger Allen Exercise,” “BAE,” “Type 2 Diabetes Mellitus,” “Peripheral Perfusion,” and “Ankle Brachial Index,” combined with Boolean operators “AND” and “OR.” Inclusion criteria comprised intervention studies published in English or Indonesian that reported outcomes related to peripheral perfusion. Results: Ten studies met the inclusion criteria. Overall, BAE was associated with significant improvements in peripheral perfusion, evidenced by increased Ankle Brachial Index values, improved capillary refill time, enhanced skin temperature and color, strengthened peripheral pulses, and reduced lower extremity pain. Several studies also reported greater benefits when BAE was combined with adjunctive interventions such as vitamin C supplementation, foot spa therapy, or music therapy. Conclusion: Buerger Allen Exercise is a low-cost, feasible, and evidence-supported non-pharmacological intervention that effectively enhances peripheral tissue perfusion in patients with type 2 diabetes mellitus and may help prevent vascular complications and improve patient well-being.